Strategi Kepala Sekolah dalam Meningkatkan Kualitas Pendidikan di Raudhatul Athfal Mau'izah Hasanah Kampar - Rusmaidah, Rusmaidah (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2019)
This study aims to analyze the principal's strategies in improving the quality of education at R.A Mau'izah Hasanah Kampar. This research employs a qualitative approach with a case study method, where data is collected through in-depth interviews, participatory observations, and document analysis. The findings indicate that the principal implements various strategies, including strengthening the school's vision and mission, enhancing teacher competencies, optimizing school management, and increasing parental and community involvement. The vision and mission are reinforced through intensive communication with all school stakeholders, while teacher competency development is facilitated through professional training and academic supervision. School management optimization is carried out by improving infrastructure and implementing a technology-based administrative system. Additionally, the principal strives to enhance parental and community engagement through school partnership programs. Although these strategies positively impact educational quality, challenges remain in their implementation, such as limited teaching staff and low parental participation. Therefore, support from various stakeholders, including the government, educators, and the community, is essential to ensure the effective implementation of these strategies.